98 Results of a phase 2, double-blind, randomized, placebo-controlled study of a reversible B cell inhibitor, XmAb®5871, in systemic lupus erythematosus (SLE). (April 2019) - Merrill, Joan T; June, Joshua; Koumpouras, Fotios; Machua, Wambui; Khan, Mohammed Faisal; Askanase, Anca D; Sheikh, Saira Z; Khosroshahi, Arezou; Foster, Paul; Zack, Debra J
Abstract : Background: XmAb5871 is a humanized anti-CD19 antibody Fc-engineered for increased affinity to FcgammaRIIb. Co-ligation of CD19 and FcgammaRIIb inhibits B lineage cells key to lupus pathogenesis. This Phase 2 study in SLE was designed to minimize background medications and placebo responses to improve interpretation of a small trial in a complex, heterogenous disease. Methods: Patients were enrolled with active, non-organ threatening disease, and treated until improved with 160 mg of IM Depo-Medrol. Immunosuppressive drugs were withdrawn except antimalarials or 10 mg/day prednisone or equivalent before randomization to IV XmAb5871 (5 mg/kg) or placebo. Study treatments were given Q14 days until Day 225 or loss of improvement (LOI), defined as SLEDAI increase 4 points OR new BILAG A or B, with investigator-rated clinical significance. At LOI, patients resumed standard of care. The primary endpoint was the proportion of subjects without LOI by Day 225 in the efficacy evaluable group (those who completed Day 225 or discontinued due to LOI or a drug-related adverse event). Patients who withdrew for other reasons were excluded from this analysis. Results: 104 patients were randomized. In the efficacy evaluable population, 42% of XmAb5871-treated subjects reached Day 225 without LOI vs 28.6% of the placebo group (p=0.18) with 40.4% vs 23.1% (p=0.06) achieving this endpoint in the ITT population. In those with LOI, no (0%) XmAb5871 patients vs 9 (30%) placebo had SLEDAI increase 7 with 3 (13%) vs 7 (23%) developing BILAG A scores. Six XmAb5871-treated patients were withdrawn for infusion-related events. The efficacy evaluable population excluded 10 placebo patients vs 2 XmAb5871 for other reasons, increasing placebo response proportions compared to the ITT population. Time to LOI was significantly longer in XmAb5871-treated patients than placebo (p=0.025, see figure 1 ). The most common AEs in XmAb5871-treated patients were transient, infusion-related gastrointestinal side effects during the 1 st or 2nd infusion. There were 8 SAEs in 7 XmAb-treated subjects, 5 in 4 placebo patients, no opportunistic infections, and no deaths. Infection rate was low compared to other SLE trials. Conclusions: Results from this small trial, designed to maximize interpretability, supports further evaluation of XmAb5871 in SLE. Funding Source(s): This study was funded by Xencor Inc.